Microdata for Social Sciences and Policy Evaluation as a Public Good - Ugo Trivellato (Institute of Labor Economics (IZA), 2017)
The balance between the right to privacy and the right to freedom of information is altered when scientific research comes into play, because of its inherent needs and societal function. This paper argues that, for research purposes, microdata should be characterised as a public good. The evolution of the rules and practices in the European Union (EU) for protecting confidentiality while allowing access to microdata for research purposes is reviewed. Two key directions are identified for further improvement: remote access to confidential data and the enlargement of the notion of 'European statistics' to include microdata produced for evaluating interventions (co)financed by the EU.
Keywords: C81; D04; H41; I38; J08; L5; 330; counterfactual impact evaluation; privacy and data protection; microdata access; intelligent openness; public policies